Osteoclacin expression during autogenous onlay bone grafts with or without resorbable collagen membrane in diabetic rats - Bernardo, Daniella Vicensotto; Tera, Tabata de Mello; de Marco, Andrea Carvalho; Melo Filho, Antonio Braulino de; Santamaria, Mauro Pedrine; Jardini, Maria Aparecida Neves (Brazilian Dental Science, 2015)
Objective: This study aimed to quantify through immunohistochemistry the expression of bone formation marker osteocalcin during the repair process of autogenous onlay bone graft, associated or not to the resorbable collagen membrane and to compare these findings with the presence of Diabetes Mellitus. Material and Methods: Sixty rats (Rattus norvegicus, albinus variation, Wistar) aged 90 days, were divided into two groups with 30 animals: test group – rats with induced diabetes; control group - normoglycemic rats. All rats received grafts on the left and right hemi-mandible with or without collagen membrane coverage, respectively. The animals were euthanized at the following periods: 0h, 7, 14, 21, 45, and 60 days. Immunohistochemistry analysis was performed by the marker osteocalcin at receptor site-graft interface. To analyze osteocalcin immunohistochemical expression, a panoramic view photograph of the graft was taken followed by two photographs at larger magnification. Results: No statistically significances at 5% level were observed between diabetic and control group with and without membrane; and diabetic and control groups with membrane coverage. Conclusion: Within the limits of this present study, it can be concluded that the osteocalcin marker might be influenced by diabetes so that it was late expressed during this condition. However, the association of the graft with the membrane could improve this delay by reaching expression values similar to those of control group.